Reproductive migration of fish and movement in a series of reservoirs in the Upper Parana River basin, Brazil - Britto, S. G. de C. [UNESP]; Carvalho, E. D. [UNESP] (Wiley-Blackwell, 2013)
AbstractThis study evaluates the effectiveness of two fish passes at two hydropower dams (Canoas I and II) in the Upper Parana basin, which form part of a cascade of three reservoirs. Fish from 12 migratory species (3089 specimens) were captured during their ascending, reproductive migration and were tagged with hydrostatic tags. The recapture data (294 specimens over two consecutive years) showed that there is a strong tendency for the maintenance of ascending migration through reservoirs with fish passes but with differences in migratory activity within the same species. No eggs, larvae or juveniles of these species were found in samples collected over 5 years in the reservoirs above the fish passes. These data suggest that fish passes have contributed to the restoration of the migratory routes of adult fish but that in the absence of suitable spawning or nursery habitats for these species; they probably act as ecological traps and do not contribute to the recruitment of the species.
Keywords: fish ladders; fish reproduction; Paranapanema River; Upper Parana basin